Alcohol consumption and risk of common cancers: evidence from a cohort of adults from the UK. (11th September 2017) - Betts, Georgina; Ratschen, Elena; Opazo Breton, Magdalena; Grainge, Matthew J
Abstract: Background: Recent guidelines from the UK recommend that men and women should drink no more than 14 units of alcohol per week. This recommendation takes into account the link between alcohol and several cancers; however, there is a dearth of high quality evidence from the UK to support this. Methods: Alcohol consumption using a detailed diary was obtained from 8670 adults representative of the UK population in 1984/5, with follow-up data from cancer registries until 2009. Hazard ratios (HRs) adjusted for several variables including cigarette smoking were calculated for cancers of the breast, lung, colorectum and prostate separately using Cox regression. Results: Units per week on a typical basis, fitted as a linear term, was associated with breast cancer in women (HR = 1.27 per 10 units/week; 95% CI 1.03–1.58) and lung cancer in men (HR = 1.16; 95% CI 1.06–1.27). Increased risks of lung (HR = 2.23; 95% CI 1.18–4.24) and colorectal (HR = 2.28; 95% CI 1.13–4.57) cancer were seen in men at 15–28 units/week along with higher levels of consumption. Some findings differed by alcohol type. Conclusions: Overall, alcohol consumption of 15–28 units/week may be harmful in men with respect to common cancers. A linear association between alcohol consumption and risk of breast cancer was observed in women.